2015
DOI: 10.1002/acr.22480
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported and Objectively Measured Physical Activity in Adults With Systemic Lupus Erythematosus

Abstract: Objective Most estimates of physical activity (PA) patterns in systemic lupus erythematosus (SLE) are based on subjective self-report measures prone to error. The aims of this study were to obtain objective measurements of PA using an accelerometer and estimates of energy expenditure based on the self-reported International Physical Activity Questionnaire (IPAQ), and to describe their relationship. Methods The “Activity in Lupus To Energize and Renew” (ALTER) study, a cross-sectional study of PA, included 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
(44 reference statements)
2
27
1
Order By: Relevance
“…The literature investigating PA behavior in SLE patients using accelerometry is limited. A study by Ahn et al 29 used accelerometry to measure MVPA in 129 SLE patients. As in our study, low levels of MVPA were demonstrated among SLE patients, with mean total MVPA of 39.6 minutes/day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature investigating PA behavior in SLE patients using accelerometry is limited. A study by Ahn et al 29 used accelerometry to measure MVPA in 129 SLE patients. As in our study, low levels of MVPA were demonstrated among SLE patients, with mean total MVPA of 39.6 minutes/day.…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, low levels of MVPA were demonstrated among SLE patients, with mean total MVPA of 39.6 minutes/day. 29 A recent study by Pinto et al 31 compared accelerometry-derived MVPA estimates between physically inactive SLE patients and physically inactive non-SLE participants. Not surprisingly, MVPA levels were very low in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerometers are able to objectively determine quantitative changes in PA. For example, self-reported time spent in moderate/vigorous PA (using the IPAQ) was higher than measurements obtained from accelerometers in one study. 16 Detailing both PA duration and intensity continuously throughout the day allows a more comprehensive description of the relationships between PA and fatigue. Finally, accelerometer responsiveness to change in PA over time has been established in rheumatic disease populations.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on the physical activity levels in SLE patients is scarce. However, a few studies have suggested that rheumatic patients may experience insufficient levels of physical activity , which could account for the reduced aerobic capacity and health‐related quality of life (HRQOL) in these patients . However, despite the notion that a physically inactive lifestyle could be detrimental in general and for rheumatic populations, there is no study assessing physical fitness and HRQOL in physically inactive SLE patients and controls.…”
Section: Introductionmentioning
confidence: 99%